A Feasibility Study on the production of Banana Blends Fabric - Blanco, Mariel M. (College of Engineering, 2000)
The Banana Blends Fabric is an all-natural fabric. It is composed of 75% polyester fiber and 25% banana fiber. The banana fiber is extracted from the trunk of the banana tree. The product is conceptualized, researched and developed by the Research and Development Department of the Philippine Textile Research Institute. The Institute aims to commercial produce the product in order to promote the use of all-natural fabric as a replacement for ramie fabric, since the Ramie Industry in the Philippines has already been declining for years now. The present blend of the banana fabric by the PTRI is best suitable as raw material for table and bed linens. This makes all home furnishing companies as our general customers. The demand for banana blends fabric was obtained by getting the past minimum capacities of all domestic home furnishing manufacturers. This data was obtained from the files of the Board of Investments. The export producing companies are also taken into account through export performance for the Garments and Export Board of the Department of Trade and Industry. Market supply was obtained through analysis of the past supply of ramie fabric, which is the most similar to banana fabric. The Market Analysis proved that the demand is greater than supply. It was from this gap and from the conducted survey that the market share was derived from. The company's initial target market share is 25% of all the local home furnishing companies, which produce both for the local and foreign markets. There are five general processes that make-up the production of banana fabric: decorticating, degumming of banana fiber, spinning, weaving, and finishing. The first two will be done in-house while the other three will be subcontracted. The raw materials for the two processes are banana trunks, chemicals for pretreatment and polyester fiber. There are two plant sites that will be utilized. The decorticating process will be done in a facility in Tanglao, Davao City where the source of banana trunk is located near. The other plant site will be in Viente Reales, Valenzuela Manila. This is where the other processes will be done and will also serve as main office for the company. The total project cost is P97,291,103.18 and will be sourced through loan financing and stockholders? equity having a ratio of 60:40. Capital will be loaned from the Development Bank of the Philippines with a 15 year amortization period and a fixed interest rate of 14.798%. Financial statements indicate high profitability with a net income of more than P20M for the first year alone. The positive net present value and a high internal rate of return value than the minimum acceptable rate of return indicate the acceptability of the project. Aside from being financially profitable, the project proved to be socially profitable also as it provides savings, businesses, and other benefits to the community. Various socio-economic measures were applied which all yielded promising results for the project. Results of all analysis made prove that, indeed, the project is feasible.